Isotopic and Petrologic Investigation, and a Thermomechanical Model of Genesis of Large-Volume Rhyolites in Arc Environments: Karymshina Volcanic Complex, Kamchatka, Russia - Bindeman, Ilya N.; Leonov, Vladimir L.; Colón, Dylan P.; Rogozin, Aleksey N.; Shipley, Niccole; Jicha, Brian; Loewen, Matthew W.; Gerya, Taras V. (Frontiers in Earth Science, 2019)
The Kamchatka Peninsula of eastern Russia is currently one of the most volcanically active areas on Earth where a combination of >8 cm/yr subduction convergence rate and thick continental crust generates large silicic magma chambers, reflected by abundant large calderas and caldera complexes. This study examines the largest center of silicic 4-0.5 Ma Karymshina Volcanic Complex, which includes the 25 × 15 km Karymshina caldera, the largest in Kamchatka. A series of rhyolitic tuff eruptions at 4 Ma were followed by the main eruption at 1.78 Ma and produced an estimated 800 km3 of rhyolitic ignimbrites followed by high-silica rhyolitic post-caldera extrusions. The postcaldera domes trace the 1.78 Ma right fracture and form a continuous compositional series with ignimbrites. We here present results of a geologic, petrologic, and isotopic study of the Karymshina eruptive complex, and present new Ar-Ar ages, and isotopic values of rocks for the oldest pre- 1.78 Ma caldera ignimbrites and intrusions, which include a diversity of compositions from basalts to rhyolites. Temporal trends in δ18O, 87Sr/86Sr, and 144Nd/143Nd indicate values comparable to neighboring volcanoes, increase in homogeneity, and temporal increase in mantle-derived Sr and Nd with increasing differentiation over the last 4 million years. Data are consistent with a batholithic scale magma chamber formed by primarily fractional crystallization of mantle derived composition and assimilation of Cretaceous and younger crust, driven by basaltic volcanism and mantle delaminations. All rocks have 35–45% quartz, plagioclase, biotite, and amphibole phenocrysts. Rhyolite-MELTS crystallization models favor shallow (2 kbar) differentiation conditions and varying quantities of assimilated amphibolite partial melt and hydrothermally-altered silicic rock. Thermomechanical modeling with a typical 0.001 km3/yr eruption rate of hydrous basalt into a 38 km Kamchatkan arc crust produces two magma bodies, one near the Moho and the other engulfing the entire section of upper crust. Rising basalts are trapped in the lower portion of an upper crustal magma body, which exists in a partially molten to solid state. Differentiation products of basalt periodically mix with the resident magma diluting its crustal isotopic signatures. At the end of the magmatism crust is thickened by 8 km. Thermomechanical modeling show that the most likely way to generate large spikes of rhyolitic magmatism is through delamination of cumulates and mantle lithosphere after many millions of years of crustal thickening. The paper also presents a chemical dataset for Pacific ashes from ODDP 882 and 883 and compares them to Karymshina ignimbrites and two other Pleistocene calderas studied by us in earlier works.